Slow City and Tourism Coexistence - Yasin Soylu; Cemile Bahtiyar Karadeniz; Koray Genç (Coğrafya Dergisi)
Certain slow cities are found to host a demand for tourism well in excess of their population. This situation being experienced in destinations whose unique features entitle them to be part of the Cittaslow movement has raised debates. Within this context, this study aims to evaluate the coexistence of tourism and slow cities based on the opinions of experts on the subject who reside in slow cities for business or personal reasons. The study has consulted within its scope the opinions of 18 academicians from nine slow cities. The results show destinations that are part of the Cittaslow movement and that also appeal to mass tourism to have lost their calm. Another important conclusion of the study is that local administrators see joining the Cittaslow movement as a marketing strategy for the destination. In the face of the existence of exemplary destinations that have lost their calm and of the marketing-oriented perspective of local administrators, the interviewees stated that relevant criteria should be used as a balancing mechanism and that sustainable tourism goals can be achieved through tourism activities that are carried out by adhering to these criteria.